Pathways to the Caliphate: Mapping Malaysian Foreign Fighter Networks in Iraq and Syria from 2012-2019 - Dass, Rueben (Terrorism and political violence, 2023)
Utilizing social media profiles, court documents and media reports, this article analyzes the Malaysian foreign fighter networks in Iraq and Syria between 2012 and 2019. It is found that the Malaysian foreign fighter phenomenon is primarily driven by charismatic personalities, i.e., influential figures who were able to attract individuals into the Middle East. The attempted movement of fighters into Iraq and Syria can be divided into three phases corresponding to three personalities; the first led by Al Qaeda linked Yazid Sufaat, the second by Ajnad al-Sham linked Lotfi Ariffin and the third by Islamic State (IS) linked Muhammad Wanndy Mohd Jedi. Contrary to popular belief, the first wave of Malaysian militants had joined Syrian-based rebel groups like Ajnad al-Sham instead of IS with the shift occurring after Lotfi Ariffin’s death in September 2014. The three phases also highlight the shift in recruitment strategy from physical recruitment to the purely online sphere. A radicalization driver model of Malaysian fighters is proposed and it is argued that the two main factors that drove Malaysian fighters into the conflict zones are (1) External factors: charismatic personalities; romanticization of jihad; moral factors and ideological factors; and (2) Internal factors: discontent with the government.